2017
DOI: 10.19044/esj.2017.v13n6p273
|View full text |Cite
|
Sign up to set email alerts
|

Dénombrement Des Populations Naturelles De Rhizobium Du Pois Chiche (Cicer Arietinum) Dans Différents Sols Du Maroc

Abstract: For the legumes cultivation, the presence of specific Rhizobium in the soil is very necessary in fact a minimum number of bacteria is essential to obtain a good nodulation. The formula used for the count of Rhizobia in soil is the most probable number (MPN) method. For this purpose, four cultivation systems were used: d1, d2, d3 and d4. The soils of the all studied regions have a natural population of Rhizobium sp cicer. The size of this population is determined by the MPN method. This has been attributed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Chickpea (Cicer arietinum L.) is one of the main legumes grown in Morocco and is mainly consumed locally [12]. The increasing demand for food, in line with population growth, requires the development and improvement of new grain-handling techniques during storage.…”
Section: Introductionmentioning
confidence: 99%
“…Chickpea (Cicer arietinum L.) is one of the main legumes grown in Morocco and is mainly consumed locally [12]. The increasing demand for food, in line with population growth, requires the development and improvement of new grain-handling techniques during storage.…”
Section: Introductionmentioning
confidence: 99%
“…But, his production only takes 10th place (Laamari et al, 2016). This low yield of chickpea is attributed to abiotic constraints but in the majority of cases to attacks by pathogens (Machehouri et al, 2017). In this regard, Bouznad et al (1990) reported that Fusarium wilt, a disease caused by Fusarium sp., soil fungi, causes significant losses in several legumes (Belabid et al, 2000).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%